Rational design of near-infrared Zn-porphyrin dye utilized in co-sensitized solar cell toward high efficiency. (January 2017) - Ding, Wei-Lu; Cui, Yi-Ming; Yang, Li-Na; Li, Quan-Song; Li, Ze-Sheng
Abstract: Co-sensitization has been considered as a helpful strategy for improving the conversion efficiency in dye-sensitized solar cells (DSSCs). In this present, Zinc porphyrin dyes 1–4 have been designed based on SM315 which has achieved the record efficiency (13%). Simultaneously, these new dyes are anticipated to replace the previous dye XW11 which is analogous to SM315 in co-sensitization system. Density functional theory (DFT) and time-dependent DFT (TDDFT) calculations have been carried out on the electronic structure and optical properties. Our results show that dye 4 can be the candidate due to its complementary absorption spectrum with co-sensitizer WS-5, sound lifetime of excited state, stronger electronic coupling with TiO2, larger electron injection rate constant, and smaller electron-hole recombination rate constant, as well as most positive-shift of the CB of TiO2 . We hope this work is helpful for design Zn-porphyrin dye with target properties to improve the performance of DSSCs. Graphical abstract: Highlights: A theoretical design of Zn-porphyrin dye in co-sensitizing system. Different π-spacers are introduced. Dye 4 can be the potential candidate. Balanced parameters can achieve the high efficiency.